Wikibooks: Introduction to Nynorsk/Phrase list
Below is a list of common phrases and phrase concepts. Typically the item or proper noun that acts as an illustration for a concept can simply be replaced without making any other changes to the sentece. Exceptions are pointed out. Eg heiter Sylve. My name is Sylve. Kva heiter du? What is your name? Eg kjem frå Wales. I come from Wales. Kvar kjem du frå? Where do you come from? Eg bur i Rendalen. I live in Rendalen. Two different prepositions are used to indicate where something is located i and på . The usage of i typically corresponds to English in ( i Egypt in Egypt ) while på typically corresponds to English on ( på Færøyane on the Faroe Islands ). Kan du norsk? Do you speak Norwegian? Eg talar ikkje norsk. I don t speak Norwegian. Eg kan berre litt norsk. I only know a little bit of Norwegian. Orsak. Kan du seia meg kvar jarnbanestasjonen er? Excuse me can you tell me where the railway station is located? Når går neste buss? When does the next bus leave? Kvar kan eg kjøpa smør? Where may I buy butter? Kor mykje kostar denne? How much does this [one] cost? Når går sola ned? When does the sun set? Når står sola opp? When does the sun rise? Kva slags vêr vert det i morgon? What will the weather be tomorrow? Kva slags dyr er dette? What kind of animal is this? Kan dette etast? / Er dette etande? Can this be eaten? Eg likar meg her. I like it here. Er det giftig? Is it poisonous? Kor lenge skal de vera her? How long will you be staying? Me er her for to veker. We are here for two weeks. = Notes = BookCat